IMPLEMENTASI UNDANG UNDANG NOMOR 14 TAHUN 2008 TENTANG KETERBUKAAN INFORMASI PUBLIK DI KABUPATEN SUMEDANG - deden haria garmana; Ai Deti; Evita Purnamasari; Nabila; Novalia Jully Anggraeni; Tagina Miftahul Zannah (LPPM UNSAP & FISIP UNSAP, 2022)
The purpose of this study was to determine the extent of the implementation of the policy of Law Number 14 of 2008 concerning Public Information Disclosure. The research method used is a qualitative research method. Data collection techniques were carried out through library research and field studies which included: Observation, Interview, Documentation Study, and Triangulation. Determination of the sample/informant in this study was carried out using purposive sampling and further analysis of the data from the Miles and Huberman models, namely: data reduction, data presentation, and drawing conclusions. Based on the results of the study, it can be concluded that there are several factors that support the implementation of the policy of Law Number 14 of 2008 concerning Openness of Public Information to increase employee awareness of their obligations. In implementing the policy of Law Number 14 of 2008 concerning the Openness of Public Information at the Communications and Information Technology Office, the overall coding and statistics of Sumedang Regency can be said to be quite good. However, there are several obstacles, namely the lack of auxiliary resources (employees) in carrying out socialization, lack of understanding from the public or not knowing at all about the policy and the lack of understanding of employees on the Policy of the Law on the disclosure of public information. Efforts to overcome these obstacles include increasing auxiliary resources (employees), conducting socialization during surveys, increasing participation and increasing employee awareness in being responsible for their duties by conducting periodic evaluations.